The examination of skeletal remains - Sarvesvaran, R.; Knight, B.H. (College of Pathologists, Academy of Medicine Malaysia, 1994)
The finding of skeletal remains is a common happening and the forensic pathologist is frequently called upon to examine the remains. It is theoretically much better for the pathologist to examine the bones at the site before they are disturbed, but this rarely happens, the bones being recovered by the public, workmen or police and brought in a jumbled condition to the pathologist. Using a systematic process of elimination such as that suggested in this paper, the maximum information can be obtained. Even so, it is common for the bones never to be identified and even the length of time the person has been dead remains unknown, due to lack of corroborative information. However, only by repeated and careful examination of a number of skeletal remains, can the pathologist hope to gain any experience. Probably the most important thing to bear in mind is the danger of being too dogmatic, especially about the date of the remains and not to mislead the investigating authorities by over-optimistic opinions.